Evaluation of a liquorice extract as a novel antimicrobial - El Awamie, Madiha (2019)
The foodborne disease listeriosis is rare but has a high mortality rate therefore it is a major concern for the food industry. It is caused by the Gram-positive bacterium Listeria monocytogenes which can survive mild food preservation conditions, (e.g., high salt and low pH), and its psychrotrophic nature means that it can grow at refrigeration temperatures. Hence listeriosis is associated with the consumption of a broad range of ready-to-eat (RTE) foods, including sliced deli meats. Liquorice extract is common a food flavouring that is known to have antimicrobial activity and this project was designed to investigate the antimicrobial activity of a waste product produced during the production of liquorice flavourings for the food industry.